2010
DOI: 10.1038/nn.2490
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomy of functional organization in the mouse auditory cortex

Abstract: The sensory areas of the cerebral cortex possess multiple topographic representations of sensory dimensions. Gradient of frequency selectivity (tonotopy) is the dominant organizational feature in the primary auditory cortex, while other feature-based organizations are less well established. We probed the topographic organization of the mouse auditory cortex at the single cell level using in vivo two-photon Ca2+ imaging. Tonotopy was present on a large scale but was fractured on a fine scale. Intensity tuning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
235
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(283 citation statements)
references
References 50 publications
31
235
5
Order By: Relevance
“…Meng et al suggest greater variation in pinwheel density across species; however, those data were derived from studies with small sample sizes using first-generation optical imaging methods that are subject to various systematic errors described in detail in [SOM of (1), figures S2 and S3 and pp. [3][4][5][6][7][8][9][10][11][12]. Our analysis unambiguously indicates that pinwheel density is a genuine invariant feature of orientation column layout over a wide range of V1 sizes and that it is insensitive to hypercolumn size (Fig.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Meng et al suggest greater variation in pinwheel density across species; however, those data were derived from studies with small sample sizes using first-generation optical imaging methods that are subject to various systematic errors described in detail in [SOM of (1), figures S2 and S3 and pp. [3][4][5][6][7][8][9][10][11][12]. Our analysis unambiguously indicates that pinwheel density is a genuine invariant feature of orientation column layout over a wide range of V1 sizes and that it is insensitive to hypercolumn size (Fig.…”
supporting
confidence: 69%
“…Siegrid Löwel, 7,8 David M. Coppola, 9 Leonard E. White, 10 Fred Wolf 1,2,7 * Meng et al conjecture that pinwheel density scales with body and brain size. Our data, spanning a 40-fold range of body sizes in Laurasiatheria and Euarchonta, do not support this conclusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5), additional nonlinear mechanisms (Vinje and Gallant, 2000;Haider et al, 2010), or noise in the measurements. This diversity is reminiscent of that observed in mouse barrel (Sato et al, 2007) and auditory cortices (Bandyopadhyay et al, 2010;Rothschild et al, 2010) where neurons with distinct properties are found next to each other.…”
Section: Functional Diversity Of Local Visual Cortical Populationsmentioning
confidence: 59%
“…Thalamocortical and intracortical input systems in primary auditory cortex A1 receives a grossly topographically organized afferent input from thalamic nuclei (Merzenich et al, 1975;Velenovsky et al, 2003;Lee and Winer, 2005;Bandyopadhyay et al, 2010;Rothschild et al, 2010). These anatomical connections are much broader, as the fine suprathreshold spectral tuning of a cortical site in A1 would suggest (Wehr and Zador, 2003;Bitterman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%